Microstructure and phase relationships of cobalts nanocrystals obtained by severe plastic deformation - Gabdrakhmanova, L.A.; Mukashev, K.M.; Muradov, A.D.; Umarov, F.F.; Yar-Mukhamedova, G.Sh. (Recent Contributions to Physics, 2019)
Nanostructured cobalt samples were obtained by method of severe plastic deformation by torsion. The high quasi-hydrostatic pressure in the working region (up to 8 GPa ) was created at installation of Bridgman anvil type. The anvils were made of tungsten carbide. he method allows to obtain the samples of high purity without pores and impurities. To carry out of X-ray studies, a DRON-7 diffractometer with cobalt radiation was used. X-ray analysis was performed according to the Bragg-Brentano method. For phase analysis the Kα lines were used. The sizes of nanocrystalline cobalt reached about 25 ¸ 50 nm. It is established that during low-temperature annealing a reset occurs in the structure of cobalt. Annealing above 3000C leads to recrystallization of its structure. Derived by severe plastic deformation by torsion nanocrystalline cobalt after heating above the phase transition temperature and cooling below this temperature retains the high-temperature fcc structure. It is shown that the nature of the hcp-fcc delayed transition can be connected with a sizes changes and a strained state of crystallites forming nanocrystalline cobalt.